Character Education Values in English Classroom Within Teachers’ Practice of Code-Mixing and Code-Switching (NOBEL: Journal of Literature and Language Teaching, 2023)
The multilingual environment in English language learning as a foreign language raises doubts regarding the existence and teaching of character education values in secondary schools. This research aims to identify character education values integrated into teacher-student interactions through code-mixing and code-switching linguistic phenomena. The research findings highlight the integration of 16 values through code-mixing and code-switching. The frequency of code-mixing by high and junior high school teachers was notably higher than code-switching. The disparity in these data outcomes reinforces the notion that the atmosphere tends to be relaxed in code-mixing, often unnoticed by speakers. Conversely, code-switching, where speakers, in this case, teachers, consciously do so with specific intentions and goals, either to integrate dominant character education values such as communication or discipline or other character education values. These findings underscore that code-switching and code-mixing are not negative elements in language learning. Instead, they serve as tools for integrating character education values among secondary school students.